PAINTING CANVA SEBAGAI INTEGRASI PENGUATAN LITERASI DIGITAL DAN KREATIVITAS MENULIS TEKS PENDEK DI SEKOLAH DASAR - Fajarwati, Salsabila; Rahmawati, Fitri Puji (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to describe the use of digital literacy painting Canva in developing students' creativity in writing short texts in Indonesian language subjects at the elementary school level and to what extent the results of using Canva digital literacy as students' creativity in writing short texts in Indonesian language subjects at the elementary school level. The research method used is a qualitative approach with the main object, namely the application of Canva application in Indonesian language learning, especially digital literacy. This research will focus on grade V students who will later use the Canva application in Indonesian language learning. The data of this study consists of two main relevant categories, namely the implementation of digital literacy and digital literacy skills after treatment. The data sources for this research will include the results of interviews and supporting documentation based on the results of the observations carried out. Furthermore, the data analysis process will be carried out using the Miles and Huberman analysis technique. The results found are 1) the use of Canva as a digital literacy painting media has a significant impact in increasing the effectiveness of Indonesian language learning at Al-Abidin ICT Elementary School and increasing student creativity, especially in writing short texts; 2) Students not only write descriptions about their hobbies, but also utilize graphic elements to strengthen the message they want to convey.